2018
DOI: 10.1155/2018/1876861
|View full text |Cite
|
Sign up to set email alerts
|

Big Data Digging of the Public’s Cognition about Recycled Water Reuse Based on the BP Neural Network

Abstract: Reuse of recycled water is very important to both the environment and economy, while the public cognition degree towards recycled water reuse also plays a key role in this process, and it determines the acceptance degree of the public towards recycled water reuse. Under the background of the big data, the Hadoop platform was used to collect and save data about the public’s cognition towards recycled water in one city and the BP neural network algorithm was used to construct an evaluation model that could affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…The results of this study were found to support the findings of similar studies conducted in the UAE (Maraqa & Ghoudi, 2012), (Wait, 2014), (Amaris et al, 2020), (Chowdhury, 2009), (Fu et al, 2018), (Hyde et al, 2017). In addition, the results agree with the factors identified in the literature to have an impact on the public acceptance of grey water reuse.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results of this study were found to support the findings of similar studies conducted in the UAE (Maraqa & Ghoudi, 2012), (Wait, 2014), (Amaris et al, 2020), (Chowdhury, 2009), (Fu et al, 2018), (Hyde et al, 2017). In addition, the results agree with the factors identified in the literature to have an impact on the public acceptance of grey water reuse.…”
Section: Discussionsupporting
confidence: 89%
“…Only 8% of the participants consider the matter not significant enough for their contribution. However, diseases and water quality concerns are the major causes of concerns, which agrees with the findings documented by (Fu et al, 2018) in their literary analysis. Social and psychological barriers concerned 27 % of the respondents, while 18 % rejected treated grey water for religious reasons as found by (Hyde et al, 2017).…”
Section: Greywater Reuse: Acceptance and Concernssupporting
confidence: 88%
See 1 more Smart Citation
“…Similar digital tools and techniques such as Information and Communication Technology (ICT), AI and Big Data could be used for providing wastewater services which includes operation and maintenance of wastewater infrastructure-sewers and wastewater treatment plants (WWTPs) and their life cycle assessment (Sousa et al, 2014;Du et al, 2019;Rebello et al, 2021). Digital technology comes very handy even when it comes to water demand management or analysing and improving public perception for using recycled water (Jayarathna et al, 2017;Fu et al, 2018). ICT solutions can be used to provide integrated solutions for water supply, water demand management and asset management (Kulkarni and Farnham 2016).…”
Section: Background Of Digitalization In Urban Watermentioning
confidence: 99%
“…The idea of KNN algorithm is to input test data when the training set data and labels are known [28], compare the characteristics of test data with those of training set, and find the first K data which is the most similar to the training set, then the corresponding category of the test data is the most frequent occurrence of K data. The classification of the algorithm is described as follows:…”
Section: Fatigue Detection and Classification Algorithmmentioning
confidence: 99%